Air-Cured Fiber-Cement Composite Mixtures with Different Types of Cellulose Fibers - Ali Murat Soydan; Abdul Kadir Sari; Burcu Duymaz; Recep Akdeniz; Bahadır Tunaboylu (Advances in Materials Science and Engineering)
This present study was carried out to check the feasibility of different cellulose fibers obtained from cropped virgin cellulose, blenched eucalyptus, and araucaria pulps through different new environmentally friendly curing processes for fiber-cement production. The aim is to introduce the different sources of cellulose fibers with lower cost to produce the “fiber-cement without autoclave” (FCWA). The slurries used in the experiments contain approximately 8% wt. of cellulose. The influence of the waste marble powder addition to the cement mixture was also studied. The physical and mechanical properties of the products which were prepared with this method under different curing conditions were investigated. The mechanical properties of eucalyptus cellulose appear to offer the best combination, especially after longer air-cure cycles. The results showed that the production of FCWA is very economical by using waste marble powders. And moreover, two new types of cellulose fibers (eucalyptus and araucaria celluloses; EuC and ArC, resp.), which provide a better density and packing in the fiber-cement leading to better modulus of rupture (MOR) and modulus of elasticity (MOE) values as virgin cellulose (ViC), are very usable for production of the fiber-cement in industrial scale.